miR-16 rescues F508del-CFTR function in native cystic fibrosis epithelial cells - Kumar, P (Gene Ther, 2015)
Cystic fibrosis (CF) is due to mutations in the CFTR gene, which prevents correct folding, trafficking and function of the mutant cystic fibrosis transmembrane conductance regulator (CFTR) protein. The dysfunctional effect of CFTR mutations, principally the F508del-CFTR mutant, is further manifested by hypersecretion of the pro-inflammatory chemokine interleukin-8 into the airway lumen, which further contributes to morbidity and mortality. We have hypothesized that microRNA (miR)-based therapeutics could rescue the dysfunctional consequences of mutant CFTR. Here we report that a miR-16 mimic can effectively rescue F508del-CFTR protein function in airway cell lines and primary cultures, of differentiated human bronchial epithelia from F508del homozygotes, which express mutant CFTR endogenously. We also identify two other miRs, miR-1 and miR-302a, which are also active. Although miR-16 is expressed at basal comparable levels in CF and control cells, miR-1 and miR-302a are undetectable. When miR mimics are expressed in CF lung or pancreatic cells, the expression of the F508del-CFTR protein is significantly increased. Importantly, miR-16 promotes functional rescue of the cyclic AMP-activated apical F508del-CFTR chloride channel in primary lung epithelial cells from CF patients. We interpret these findings to suggest that these miRs may constitute novel targets for CF therapy.